Perception of Mosque Accountability: Insights from Jogokariyan Mosque - Ekaviana, Dessy (Akuntansi research UGR, 2024)
Abstract Purpose: This study aims to explore the concept of accountability as understood by the leadership (Takmir) of Jogokariyan Mosque, focusing on how Islamic values shape their governance practices. Methodology: A qualitative approach was employed within an interpretive paradigm to uncover the nuanced perceptions of accountability among the mosque’s leadership. Data were collected through in-depth interviews and observations to capture the deeper meanings behind their practices. Findings: The research identifies three core interpretations of accountability rooted in the concept of amanah (trustworthiness): (1) fulfilling responsibilities according to assigned duties, (2) transparently reporting on those responsibilities to the public, and (3) carrying out tasks with a strong personal commitment. The first interpretation emphasizes concrete actions through four stages: mapping, service delivery, empowerment, and guidance. The second highlights the importance of transparency in maintaining public trust, while the third underscores the social dynamics of accountability, focusing on authority, loyalty, and integrity. Implications: These findings provide valuable insights into how religious institutions can balance spiritual, social, and moral dimensions of accountability with contemporary governance challenges. The Jogokariyan Mosque leadership demonstrates how Islamic values can be integrated into governance, offering a model for value-driven management that fosters both spiritual growth and community development. Originality: This study presents a unique perspective on amanah-based accountability within religious institutions, particularly from an Islamic governance lens. By examining the case of Jogokariyan Mosque, the study contributes to broader discussions on accountability in non-profit and faith-based organizations, highlighting the potential for religious institutions to model transparent, ethical leadership in complex social contexts.